GE_GERICHTE C/7578/2014 vom 13. Juni 2016 - GE Cour de justice (2016)
RÉSILIATION IMMÉDIATE ; JUSTE MOTIF ; ARRESTATION ; DÉTENTION PROVISOIRE ; DROIT AU SALAIRE ; RESPONSABILITÉ CONTRACTUELLE ; TRAVAILLEUR ; DOMMAGE | CO.337; CO.337c.1; CO.324a